The Effect of Birthing Balls on the Length of First Stage Labor among Primigravidas at the Barokah Main Clinic Bandung City in 2021 - Rukmaini; Oktaviani, Feni; Suciawati, Anni (Rajaki of Tulip Medika Publisher, 2023)
Background: Labor and birth are physiological events and normal. Delivery is said to be normal if the process is full term (37-42 weeks) without any complications. Birth ball is a technique to help progress labor that can be used during the first stage of labour. Until now, not much is known and not familiar with birth balls, even though birth balls are very effective in speeding up the delivery process. The advantage of using this birth ball is that it increases blood flow to the uterus, placenta and baby, relieves pressure and can increase the output of the pelvis by as much as 30%, provides comfort for the knees and ankles, provides counter-pressure on the perineum and erect thighs. Objective: To determine the average duration of the first stage of labor in primigravidas using a birth ball and without using a birth ball and to determine the effect of a birthing ball on the duration of the first stage of labor in primigravidas Methodology: This study used a quasi-experimental method with a Randomized Two-Group, Posttest only design. Held at the Barokah Main Clinic in Bandung City. The time of the research was carried out from June to July 2021. The research sample was primigravida in the first stage of the birth of 30 respondents with data analysis using the Mann Whitney test and independent sample t-test. Results: Based on the results of the study using the Mann Whitney test and the independent t-test, the p value <0.05 was obtained. Conclusion: There is a difference in the average duration of the first stage of labor in primigravidas using a birth ball and without using a birth ball. It is expected that women in labor can know the function of the birth ball so that they can maximize the use of the birth ball in the delivery process.